Device-Sizing and Associated Complications With Left Atrial Appendage Occlusion: Findings From the NCDR LAAO Registry. (6th December 2022) - Sandhu, Amneet; Varosy, Paul D.; Du, Chengan; Aleong, Ryan G.; Tumolo, Alexis Z.; West, J. Jason; Tzou, Wendy S.; Curtis, Jeptha P.; Freeman, James V.; Friedman, Daniel J.; Hess, Paul L.
Abstract : Background: Left atrial appendage occlusion is an important alternative to anticoagulation in select patients with nonvalvular atrial fibrillation. Trends in real-world device sizing and associated short-term complications have not been characterized. Methods: Using the National Cardiovascular Data Left Atrial Appendage Occlusion (NCDR LAAO) Registry, patients who underwent left atrial appendage occlusion with a Watchman 2.5 device from January 1, 2016, to June 30, 2020, were identified. Patients were stratified by device size based on left atrial appendage orifice size, and categorized as receiving a device that was undersized, oversized, or per manufacturer recommendation. Relationships between device sizing and short-term outcomes, including pericardial effusion, device embolism, and significant leak, were assessed. Results: Of the 68 456 patients, 6539 (10.5%) of patients received undersized devices, 17 791 (26.0%) according to manufacturer recommendations, and 44 126 (64.4%) received an oversized device. The 27-mm device was most commonly deployed [21 736 (31.8%)], whereas the smallest and largest devices (21 and 33 mm) were least commonly deployed [7695 (11.2%) and 9077 (13.3%), respectively]. Compared with manufacturer recommended sizing, there was no difference in the odds of pericardial effusion for either undersized (1.048 [95% CI‚ 0.801–1.372]; P= 0.733) or oversized (1.101 [95% CI‚ 0.933–1.298]; P= 0.254) devices. Similarly, relative to manufacturer recommended sizing, the odds of a composite adverse outcome of device migration or embolization and significant peridevice leak at 45 days were similar among undersized devices (1.030 [95% CI‚ 0.735–1.444]; P= 0.863) and favorable for oversized devices (0.701 [95% CI‚ 0.561–0.876]; P= 0.002) devices, primarily driven by lower odds of leak. Selection of oversized devices increased significantly over the study period (from 60.3% in 2016 to 66.0% in 2020; P <0.001). Conclusions: Among patients undergoing left atrial appendage occlusion with the first-generation Watchman device, receipt of oversized devices was common and increased over time. The high prevalence of oversizing was associated with lower odds of significant leak or device embolization without increased odds of other adverse events.